Chapter On the optimal weight function in the Goldston-Pintz-Yıldırım method for finding small gaps between consecutive primes - Farkas, Bálint (De Gruyter, 2013)
We work out the optimization problem, initiated by K. Soundararajan, for the choice of the underlying polynomialused in the construction of the weight function in the Goldston-Pintz-Yıldırım method for finding small gaps between primes.